chr(38)quot;Madame de Beauvoir, c’est moichr(38)quot;: une archéologie féministe de la pensée française contemporaine (Sartre, Lévi-Strauss, Bourdieu) = chr(38)quot;Madame de Beauvoir is mechr(38)quot;: a feminist archeology of contemporary French thought (Sartre, Levi-Strauss, Bourdieu) - Cormann, Grégory (Veritas)
Sartre, Lévi-Strauss and Bourdieu strongly structured the intellectual (and institutional) space of the human sciences in France from the 1950s to the mid-1980s. Despite the political but also philosophical importance of the Second Sex, despite its commitments and its celebrity planetary associated with that of Sartre, the philosophy of Simone de Beauvoir remains, however, most of ten confined to an interstitial role. She would have laid the foundations of her thought in the margins of existentialism and structuralism (we know that Beauvoir had the Elementary Structures of Kinship since 1947). Our hypothesis sets out to reverse this hermeneutic framework: it will be argue here that Beauvoir's interpretation of Lévi-Strauss's structuralism in Les Temps Modernes in 1949 is decisive for understanding the relations between existentialist phenomenology and structural anthropology. Far from being secondary, the question of the feminine and its power of composition and creation seems to be the riddle of Sartre's and Lévi-Strauss's contributions to a critical theory of society, but also that of Bourdieu, whose entire work until The Misery of the World inherits underthe hand of Beauvoir's legacy to contemporary French thought. Summarized by Sartre in a passage of Questions of Method devoted to Flaubert by the question chr(38)quot;On what condition is a feminisation of experience possible?chr(38)quot;, the aim of this article is therefore to lay the foundations for a feminist archeology of contemporary French thought